Lower Bound Beliefs and Long-Term Interest Rates - Grisse, Christian (IMF Working Papers; Working Paper ;, 2017)
We study the transmission of changes in the believed location of the lower bound to longterm interest rates since the introduction of negative interest rate policies. The expectations hypothesis of the term structure combined with a lower bound on policy rates suggests that normal policy transmission is reduced when policy rates approach this lower bound. We show that if market participants revise downward the believed location of the lower bound, this may in itself reduce long-term yields. Moreover, normal policy transmission to long-term rates increases. A cross-country event study suggests that such effects have been empirically relevant during the recent negative interest rate episode.